När kallet ställs på sin spets: Pensionering ur ett existenssociologiskt perspektiv (Sociologisk Forskning, 2016)
When the calling is brought to a head: Retirement from an existential sociology perspectiveIn this article we analyze how the meaning and value of work can emerge, be defined and redefined in relation to the coming of retirement, by focusing individuals with dedicated work approaches interpreted as a calling. By relying on an existential sociology framework we analyze the retirement process as an existential imperative, e.g. life phases or processes where questions on meaning and life quality become prominent. For the interviewees, the day of retirement becomes a sort of a road sign that – depending on the distance of time to the point of retirement – has intensified existential questions and the meaning of work. The article explores the defining dimensions of a calling as found in the interviewees dedicated work approaches. We address the types of problems and opportunities that arise when the interviewees are soon to retire and their associated strategies: listening to a calling on ”standby”; learning not to listen to one’s calling, listening to a calling from a private sphere and project the calling’s commitment to other activities.
Keywords: calling; existential imperative; existential sociology; retirement; Sweden